Kinetika vulkanisasi dan sifat mekanis komposit acrylonitrile butadiene rubber (NBR) - Yuniari, Arum; Setyorini, Ike; Mayasari, Hesty Eka (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
The aim of this research was to study the effect of vulcanization temperature on mechanical properties and curing kinetics of NBR composites. The composites were formulated by using two types of carbon black i.e. N-330 and N-774. The curing kinetics was determined using Moving Die Rheometer. The network formation processes were related to torque and time. The vulcanizates were obtained by compression molding in a hydraulic press at 150Â°C and 160Â°C. The mechanical properties observed include tensile strength, elongation at break, hardness, and tear strength. Kinetics studies were approached by Arrhenius equation and the reaction mechanism was assumed following first order reaction. The results showed that curing kinetics can be approached by the equation from the rheometer data. The surface area of carbon black strongly influenced the mechanical properties and rate constant (k) of NBR composite. Carbon black N-330 can be used as a desirable reinforcing filler which gave a higher mechanical properties than the other type of carbon black.Keywords: curing kinetics, NBR, temperature, mechanics.